Walk 3 WAR AND PEACE - -, - (project baikal, 2011)
Memorial Complex «Tank “Irkutsky Komsomolets”» V.P.Sukhachev’s Estate Park Sketch of Development along Dekabrskikh Sobyty Street and Ushakovka-Angara Green Axe Trade Unions ‘ Recreation Center for 800 seats on Dekabrskikh Sobyty Street 1200-seat Hostel for Institute of National Economy on Sovetskaya Street Monument to Irkutsk Citizens Killed on Military Duty